Analisis Pemberhentian Penyaluran Zakat Produktif Bergulir Di Baitul Mal - Murni, Seri; Ashal, Farid Fathony; R, Rosmiana (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to determine the background or consideration of the distribution of revolving productive zakat in the form of machine and boat rickshaws and to analyze the causes of the dismissal of revolving productive zakat transfers in the Baitul Mal City of Banda Aceh. This type of qualitative research, data validity techniques using triangulation method, then using descriptive analysis. As for the background or consideration of the distribution of productive zakat in the form of machine rickshaws, that is first, the machine rickshaw is one of the transportation needed by the community after the tsunami, secondly, mustahik requires a lot of machine rickshaws to run its business and thirdly, the becak driver is easily run by mustahik. Then the distribution of aid in the form of a boat to help mustahik who live in coastal areas and work in the ocean. The cause of the dismissal of productive zakat distribution is first, problematic financing or bad financing. Second, the distribution of productive zakat in the form of a pedicab is stopped to avoid traffic congestion.